Creativity and Innovation: Practices Amongst Students of a Product Development Competition - Anita Ismail; Farah Laili Muda @ Ismail; Latifah Abdul Latiff; Siti Nor Baya Mat Yacob; Mohammad Aizuddin Abdul Aziz; Hisham Muhammad Taky Eldin Kandil (Universiti Sains Islam Malaysia, 2024)
The purpose of this paper is to investigate the state of creativity and innovation on product development among students who participated in the Islamic Innovation Student Competition (i-REKA) 2017 at Universiti Sains Islam Malaysia (USIM). The study employed the quantitative approach through a survey instrument design. Data were collected using questionnaires, and the constructs used were developed from prior research and previously tested for reliability. A total of 147 questionnaires were analyzed from the respondents in this study. Descriptive statistics were used to analyze the characteristics of the respondents including frequency, percentage, mean, and standard deviation, while the multivariate technique that was employed was regression. The findings revealed that significant relationships exist between the state of creativity and innovation among students of products development competition. These findings may provide a distinctive perspective on the concept of creativity and innovation and its necessity in the Islamic educational system for the contemporary modern era.